Preclinical evaluation of 3D-Printed orthodontic aligners using an electro-typodont model - Al Shalabi, Ammar A.; Malik, Shaima; Kim, Hoon; Alhotan, Abdulaziz; Ghoneima, Ahmed; Elshazly, Tarek M. (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectivesThe use of 3D printing in orthodontic aligner production addresses several limitations of conventional thermoforming. However, existing experimental techniques for evaluating aligner efficacy remain restricted. This study aims to introduce a novel experimental approach employing an electric typodont model to assess the effectiveness of 3D-printed orthodontic aligners in correcting rotation of the maxillary right central incisor (Tooth 11).Materials and MethodsAn electric typodont, equipped with heat-activated wax blocks, simulated four rotational severities of Tooth 11: 22°, 32°, 42°, and 52°. Digital scans were processed in Maestro 3D software to design virtual treatment plans, from which four sequential aligners were fabricated per severity level. In total, 240 aligners were 3D-printed, using Tera Harz TC-85 resin, in three thicknesses: 0.50, 0.75, and 1.00 mm. Each aligner underwent a 10-minute heating cycle, followed by a 10-min cooling period. Tooth rotation was measured manually using a protractor relative to a fixed baseline. The procedure was repeated five times per subgroup, with repositioning guided by custom guiding stents.ResultsAcross all aligner thicknesses, 80.0%–93.1% of the planned rotational correction was achieved by the fourth aligner, leaving residual rotations of approximately 4°–5°. Higher initial rotations resulted in a greater percentage of corrections (p < 0.001). The 0.50-mm and 1.00-mm aligners demonstrated faster early-stage correction, whereas the 0.75-mm aligner exhibited a more gradual and consistent derotation pattern throughout the treatment stages (p < 0.001).ConclusionThe electric typodont appears to be a reliable pre-clinical tool for evaluating the effectiveness of aligners. Furthermore, 3D-printed aligners successfully achieved incisor derotation without the use of attachments. Furthermore, while variations in aligner thickness influenced the dynamics of derotation, they did not alter the ultimate correction outcome.